The The Relationship between Body Image and Self-Esteem among Tuberculosis (TB) Patients at Puskesmas - Anggraeni, Meisty; Suprayitno, Edy (Universitas 'Aisyiyah Yogyakarta, 2025)
Tuberculosis (TB) is one of the leading causes of death worldwide. TB patients often face challenges related to changes in body image, which are influenced by physical, economic, social, and psychological factors. Physically, patients may experience drastic weight loss, shortness of breath, paleness, and persistent coughing. Economically, TB can lead to a decrease in employment and income. Socially, it can result in stigma as part of a broader social process. Psychologically, TB can increase emotional stress and feelings of disappointment. These changes in body image can also impact a patient’s self-esteem. This study aims to examine the relationship between body image and self-esteem among TB patients at Puskesmas (Community Health Centers) in Yogyakarta City. This was a quantitative study using a cross-sectional design. The sampling technique used was purposive sampling. A total of 56 respondents over the age of 15, all undergoing TB treatment and resistant to TB medication, participated in the study. Data were analyzed using the Spearman Rank correlation test. The results of the Spearman Rank test showed a p-value of 0.847 (>0.05), indicating that there is no significant relationship between body image and self-esteem in TB patients at Puskesmas in Yogyakarta City. It can be concluded that body image is not significantly related to self-esteem among TB patients in this setting. Nevertheless, respondents continued their treatment regularly and maintained both their body image and self-esteem.